Cytochrome Oxidase C Subunit I (COI) for Identification and Genetic Variation of Loaches (Nemacheilus fasciatus) - Amalia Ayuk Riyadini; Maheno Sri Widodo; Mohamad Fadjar (Research Journal of Life Science, 2020)
Nemacheilus fasciatus is an Indonesian freshwater fish species that can be found in river waters on Java. This fish has a morphological similarity between species. This study aims to identify species of samples found and know their genetic kinship. This study used the Cytochrome Oxidase subunit I (COI) gene as a molecular marker, and then the results were analyzed using MEGA X software. The genetic structure and phylogeny of N. fasciatus sequences were combined with outgroup species from GenBank and analyzed using Maximum Likehood (ML), Pairwise Genetic Distance and Bootstrapping Phylogeny Model of Kimura 2 Parameters. The results showed that the primary pairs of LCO1490 and HCO2198 used to amplify the sample N. fasciatus with COI as a marker. The nucleotide frequencies of these loaches are A=26.5%, T=23.8%, C=19.9% and G=29.9%. The estimated Transition/Transversion bias (R) is 0.60. The number of haplotype diversity (Hd) was 0.972, and nucleotide (Pi) diversity was 0.05115. The kinship of N. fasciatus compared to the outgroup is closer to N. pallidus than N. chrysolaimos. Research needs to be conducted with a larger sample size for the genetic diversity of N. fasciatus in Indonesia.